EFL Pre-Service Teachers’ Perception in the Implementation of the Program Kampus Mengajar toward The Pedagogical Competence - Setia, Cane; Upa, Yunika; Nurcahyoko, Kunto (JELITA, 2025)
This study explores EFL Pre-service teachers’ perception in the implementation of the Program kampus Mengajar toward the pedagogical competence. Using descriptive qualitative method, three participants from Universitas katolik Santo Agustinus Hippo (Program Kampus Mengajar Batches 6 and 7) were purposively selected. Data were collected through semi-structured questionnaires and in-depth interviews, then analyzed through thematic analysis namely data reduction, data presentation, conclusion drawing, and source triangulation. The results showed significant improvements in five pedagogical aspects: content knowledge, knowledge of pedagogical approach, classroom management skills, student management skills, and subject management ability. The participants also reported improved adaptation of teaching strategies in 3T schools, pedagogical creativity, reflective practice, and professional skills (communication, creativity, adaptability) through authentic experiences. The study concluded that the Program Kampus Mengajar effectively bridges the theory-practice gap in disadvantaged areas, recommending a structured mentor framework, locally-appropriate 3T training modules, and longer practicum duration to optimize outcomes.